Integration of Different Wireless Technology and Methodology for Future Generation of Wireless Communication - Singh, Shashank; Shukla, Himanshu Kumar; Sharma, Rohit (International Journal of Computer Sciences and Engineering, 2025)
There are many technologies and methodologies present to support existing wireless mobile communication. We propose a concept to integrate best methodologies and technologies that suits the future generation in terms of high system, spectral efficiency, and energy efficiency etc. Our approach to achieve requirement of next or upcoming generation 1stly we analyze best technology and methodologies (like multi input multi output (MIMO), orthogonal frequency division multiple access (OFDMA), Direct-device to device (D2D) communication, MIMO, Mm wave, Spatial modulation, Radio access technology etc.) of each generation and then check the possibility of integration of technologies and methodologies. And design architecture with integrated technologies and methodologies with respect to future generation. So, we check the possibility and try to integrate various technologies and methodologies of different generation to fulfill the requirement of next generation.